Teachers’ willingness to change in adapting to online learning during the covid-19 pandemic - Reni Herawati; Heru Kurnianto Tjahjono; Ika Nurul Qamari; Sri Handari Wahyuningsih (LPMPP Universitas Negeri Yogyakarta, 2022)
This study aimed to highlight the view of educators on the teachers’ willingness to change in adapting to online learning due to the Coronavirus disease 19 (COVID -19) pandemic. The sudden shifting required readiness to facilitate both synchronous and asynchronous learning interactions. The results of previous studies on the dissatisfaction with the online learning quality during the pandemic triggered this study. Teachers preferred to use task-based learning and resisted incorporating technology in the learning process. The limited literature provided a study gap investigated in the present study. Therefore, the real-time virtual focus group discussions were carried out to obtain viewpoints about teachers’ willingness to change in which 31 participants, including teachers, principals, and supervisors, shared their viewpoints. Moreover, dynamic discussions were conducted through brainstorming using Mentimeter, collecting viewpoints via zoom poll, and discussion engagements in the primary and breakout rooms. Content analysis revealed three categories: willingness to learn, try, and be open. The result provided novelty essential as a new perspective and proposed possible solutions to address the problems shifting from regular to online learning in Indonesia. Finally, this study recommends future investigation of teachers’ willingness to change as a new concept of professional development in establishing quality learning.